Assessing the effectiveness of vehicle emission regulations on improving perinatal health: a population-based accountability study. (9th October 2020) - Willis, Mary D; Hill, Elaine L; Kile, Molly L; Carozza, Susan; Hystad, Perry
Abstract: Background: Since the 1990s, extensive regulations to reduce traffic-related air pollution (TRAP) have been implemented, yet the effectiveness of these regulations has not been assessed with respect to improving infant health. In this study, we evaluate how infant health risks associated with maternal residences near highways during pregnancy have changed over time. Methods: We created a population-based retrospective birth cohort with geocoded residential addresses in Texan metropolitan areas from 1996 through 2009 ( n  = 2 259 411). We compared term birthweight (37–42 weeks of gestation) among maternal residences <300 m from a highway (high TRAP exposure) ( n  = 394 346) and 500–3500 m from a highway (comparison group) ( n  = 1 865 065). We implemented linear regressions to evaluate interactions between high TRAP exposure and birth year, adjusting for demographics, socioeconomic status and neighbourhood context. In addition, we used propensity score matching to further reduce residual confounding. Results: From 1996 to 2009, outdoor NO2 decreased by 51.3%, based on regulatory monitoring data in Texas. Among pregnant women who resided in the high TRAP zone during pregnancy, interaction terms between residential location and birth year show that birthweight increased by 1.1 g [95% confidence interval CI): 0.7, 1.5) in unadjusted models and 0.3 g (95% CI: 0.0, 0.6) in matched models. Time-stratified models also show decreasing impacts of living in high TRAP areas on birthweight when comparing infants born in 1996–97 with 2008–09. Sensitivity analyses with alternative exposure and control groups show consistent results. Conclusions: Infant health risks associated with maternal residence near highways have reduced over time, paralleling regulatory measures to improve exhaust pipe emissions.